How does population aging affect the effectiveness of monetary and fiscal policies? - Naoyuki Yoshino; Hiroaki Miyamoto (Asian Development Bank Institute (ADBI), 2019)
This paper studies how population aging affects macroeconomic performance and the effectiveness of macroeconomic policies. By using a new Keynesian dynamic stochastic general equilibrium model with heterogeneous households, we find that the effectiveness of monetary policy diminishes as population aging proceeds. We then examine how population aging modifies the fiscal policy effect by estimating fiscal multipliers in both aging and non-aging economies. We find that population aging weakens the effectiveness of fiscal stimulus. Our analyses suggest that neither monetary policy nor fiscal policy would be effective in aging economies, and structural reform measures would have a more important role.
Keywords: E52; E62; J10; 330; population aging; monetary policy; fiscal policy; DSGE; fiscal multipliers